Application of modern pharmacological technologies to search for new ergogenic aids in sports: an empirical analysis and actual outcomes - Иван Чекман; Лариса Гунина (National University of Physical Education and Sport of Ukraine, 2017)
As a result of the analysis of predicted biological and pharmacological properties of levocarnitine and melatonin molecules through the use of modern quantum pharmacological techniques, a high degree of agreement is demonstrated with published empirical data from studies in athletes. Existence of new, not described earlier in the literature properties of these biologically active compounds offers great opportunities for their application in new areas of pharmacology and medicine of sport. The high degree of agreement between the data produced by quantum pharmacological analysis and actual results of experimental research substantiates the full appropriateness of the use of these modern techniques in the field of sports pharmacology. This will help to significantly increase the accuracy of prediction of pharmacological properties of new ergogenic aids, to save material resources and time expended on the search for substances that can be used later as a means of enhancing sports performance and accelerating recovery processes.